Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Have to evaluate this limit, but trigonometry part is :(

$$\lim_{x\to 0} \dfrac{1-\cos^3 x}{x\sin2x}.$$

Had written the denominator as $2x\sin x\cos x$, no idea what to do next. Please help...

share|cite|improve this question
Can you use Taylor series? – Hakim Aug 5 '14 at 12:40
@Hakim: bro no idea on taylor series... simplification of the trigonometric term will help... :( – Adarsh Aug 5 '14 at 12:47
up vote 5 down vote accepted

$$\eqalign{ \lim_{x\to 0} \dfrac{1-\cos^3 x}{x\sin2x} &=\lim_{x \to 0} \dfrac{(1-\cos x)(1+\cos x+\cos^2 x)}{2x\sin x\cos x}\\ &=\lim_{x \to 0} \dfrac{3(1-\cos x)}{2x\sin x}\\ &=\lim_{x \to 0} \dfrac{6\sin^2(x/2)}{4x\sin(x/2)\cos(x/2)}\\ &=\lim_{x/2 \to 0} \dfrac{3\sin(x/2)}{4(x/2)}\\ &=\dfrac{3}{4}. }$$

share|cite|improve this answer
Nice method. That's pretty neat! – Kari Aug 5 '14 at 12:57

Otherwise using: $$a^3-b^3=(a-b)(a^2+ab+b^2)$$ $$\eqalign{ \lim_{x\to 0} \dfrac{1-\cos^3 x}{x\sin2x} &=\lim_{x\to 0} \dfrac{(1-\cos x)(1+\cos x+\cos^2x)}{2x\sin x\cos x}\\ &=\frac32\lim_{x\to 0} \dfrac{(1-\cos x)}{x\sin x\cos x}\\ &=\frac32\lim_{x\to 0} \dfrac{\frac{(1-\cos x)}x}{x\frac{\sin x}x\cos x}\\ &=\frac32\lim_{x\to 0} \dfrac{(1-\cos x)}{x^2\cos x}\\ &=\frac32\lim_{x\to 0} \dfrac{(1-\cos x)}{x^2\cos x}.\frac{1+\cos x}{1+\cos x}\\ &=\frac32\lim_{x\to 0} \dfrac{1}{\cos x(1+\cos x)}.\left(\frac{\sin x}{x}\right)^2\\ &=\frac32\times\frac1{1\times2}\times1^2=\frac34.}$$

Using Taylor series: $$\cos x =1-x^2/2+O(x^4)$$ $$\sin x =x-x^3/6+O(x^5)$$ $$(1+x)^n=1+nx+O(x^2)$$ So, $$\eqalign{ \lim_{x\to 0} \dfrac{1-\cos^3 x}{x\sin2x} &=\lim_{x\to 0} \dfrac{1-(1-x^2/2+O(x^4))^3}{x(2x+O(x^3))}\\ &=\lim_{x\to 0} \dfrac{1-(1-3x^2/2+O(x^3))}{(2x^2+O(x^3))}\\ &=\lim_{x\to 0} \dfrac{3x^2/2+O(x^3)}{2x^2+O(x^3)}=\frac34.}$$

Using L-Hospital Rule: $$\eqalign{\lim_{x\to 0} \dfrac{1-\cos^3 x}{x\sin2x}& =\lim_{x\to 0} \dfrac{3\cos^2 x.\sin x}{\sin2x+2x\cos2x}\\ &=\lim_{x\to 0} \dfrac{3\sin x}{\sin2x+2x\cos2x}\\ &=\lim_{x\to 0} \dfrac{3\cos x}{2\cos2x+2\cos2x-4x\sin2x}\\ &=\frac{3\times1}{2\times1+2\times1-4\times0}=\frac34.}$$

share|cite|improve this answer

You can break the limit into two parts:

$$\eqalign{ \lim_{x\to 0} \dfrac{1-\cos^3 x}{x\sin2x} & =\lim_{x\to0}\dfrac{\sin^2x+\cos^2x-\cos^3x}{x\sin2x} \\ &=\lim_{x\to0}\dfrac{\sin^2x+\cos^2x(1-\cos x)}{x\sin2x} \\ &=\lim_{x\to0}\color{darkmagenta}{\dfrac{\sin^2x}{x\sin2x}}+\color{darkblue}{\dfrac{\cos^2x(1-\cos x)}{x\sin2x}}. }$$

The first part can be written as $\color{darkmagenta}{\tfrac{\tan x}{2x}}$ and the second as $\color{darkblue}{\tfrac{{\cos x\tan\left(\tfrac x2\right)}}{2x}}$. Hopefully those two will be easier to deal with than the original limit. ;-)

share|cite|improve this answer

After two applications of L'Hôpital's rule: $$ \displaystyle \begin{aligned} \lim_{x \to 0} \left( \dfrac{1-\cos^3 (x)}{x\sin (2x)} \right) & \ = \ \lim_{x \to 0} \left( \dfrac{3\sin (x) \cos^2 (x)}{\sin (2x) + 2x\cos (2x)} \right) \\ & \ = \ \lim_{x \to 0} \left( \dfrac{3\cos^3 (x) - 6\cos (x) \sin (x)}{4\cos (2x) - 4x \sin (2x)} \right) = \ ? \end{aligned} $$

share|cite|improve this answer

By Taylor series $$\cos x \sim_0 1 - \frac{x^2}{2}, \,\sin 2x \sim_0 2x\, \text{ and }\,\Big(1-\frac{x^2}{2}\Big)^3 \sim_0 1 - \frac{3x^2}{2}$$ so $$\dfrac{1-\cos^3 x}{x\sin2x} \sim_0 \frac{1 - \Big(1-\frac{x^2}{2}\Big)^3}{2x^2} \sim_0 \frac{ \frac{3x^2}{2} }{2x^2} = \frac{3}{4}.$$

share|cite|improve this answer
Thanks for the explanation bro... well I got to learn Taylor series now.. :) – Adarsh Aug 5 '14 at 13:33

$$\lim_{x \to 0}\frac{1-\cos^3x}{2x^2} \cdot \lim_{x \to 0}\frac{2x}{\sin(2x)}$$ The right limit is equal to 1. For the left limit, you may use the rule of de l'Hôpital: $$\eqalign{ \lim_{x \to 0}\frac{1-\cos^3x}{2x^2}&=\lim_{x \to 0}\frac{3\cos^2 x \sin x}{4x}\\ &=\lim_{x \to 0}\frac{-6\cos x \sin^2 x + 3 \cos^3 x}{4}\\ &=\frac{-6\cdot 0 + 3 \cdot 1}{4}\\ &=\frac{3}{4}. }$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.